1992
DOI: 10.1046/j.1537-2995.1992.32893032106.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with hepatitis B or C markers or elevated alanine aminotransferase level among blood donors on a tropical island: the Guadeloupe experience

Abstract: Donated blood is currently screened for hepatitis B surface antigen (HBsAg), antibody to hepatitis B core antigen (anti-HBc), antibody to hepatitis C virus (anti-HCV), and alanine aminotransferase (ALT) levels to prevent posttransfusion hepatitis. A prospective study of 2368 blood donors was carried out in Guadeloupe (French West Indies) with a view to determining the risk factors associated with serologic abnormalities. Blood donors included in the study had to complete a questionnaire. Statistical analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Sharing razors (83,84), sharp objects (nail clippers, manicure cutters, scissors) (83), tooth brush (85), non-sharp objects (shower scrapper, towels, combs) (48,(86)(87)(88), and some folk medical practices including cupping/ventosed bloodletting (known in the Arab world as hijama) (37,(89)(90)(91), circumcision and ritual clitorodectomy (36,41,69,76,92) were studied as risk factors for HCV infection only in the late 1990s. Similarly, the role of barber was only addressed during the last decade.…”
Section: Discussionmentioning
confidence: 99%
“…Sharing razors (83,84), sharp objects (nail clippers, manicure cutters, scissors) (83), tooth brush (85), non-sharp objects (shower scrapper, towels, combs) (48,(86)(87)(88), and some folk medical practices including cupping/ventosed bloodletting (known in the Arab world as hijama) (37,(89)(90)(91), circumcision and ritual clitorodectomy (36,41,69,76,92) were studied as risk factors for HCV infection only in the late 1990s. Similarly, the role of barber was only addressed during the last decade.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent scientific data on the prevalence of viral hepatitis infections in Guadeloupe were reported by Fest et al [1,2] in 1993 among blood donors. They showed that hepatitis B surface antigen (HBsAg) was present in 3.1%, hepatitis B core antibodies (anti-HBc) in 22.1% and anti-hepatitis C virus antibodies (anti-HCV) in 0.8% of the population.…”
Section: Introductionmentioning
confidence: 99%
“…Data on HCV infection in the Caribbean region are scarce. A few studies have reported a similar HCV infection prevalence to that in the United States and Europe (2,6,11,16,35), but the HCV genotype distribution remains to be determined. A predominance of HCV subtype 1a has been described in the Dominican Republic (23) and in Puerto-Rico (30), but no information is available on HCV genotype distribution in the Lesser Antilles archipelago.…”
mentioning
confidence: 95%